2020
DOI: 10.1590/1806-9126-rbef-2019-0321
|View full text |Cite
|
Sign up to set email alerts
|

Uma metodologia de custo zero para medida de atrito de rolamento em VANTs

Abstract: Resumo A despeito do fato que medidas do coeficiente de atrito de rolamento são importantes em diversas áreas, o assunto em geral não é adequadamente tratado no ensino médio ou superior. Tal situação priva o estudante do conhecimento dos recursos experimentais utilizados para medir o coeficiente de atrito, além de comprometer o entendimento do fenômeno. Além disso, certos pares de materiais de interesse para a engenharia simplesmente não são encontrados na literatura, como no caso dos pneus utilizados em veícu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The extensive use of our analytical results since 2015 in a toolbox developed by the authors showed that S to and S are rather sensitive to the value of µ e used. To tackle the problem, we developed a simple methodology [8] to measure µ r for the UAVs tested. The values obtained are considerably larger than the available values for large pneumatic tires over concrete used for the Cessna (truck tires, actually).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The extensive use of our analytical results since 2015 in a toolbox developed by the authors showed that S to and S are rather sensitive to the value of µ e used. To tackle the problem, we developed a simple methodology [8] to measure µ r for the UAVs tested. The values obtained are considerably larger than the available values for large pneumatic tires over concrete used for the Cessna (truck tires, actually).…”
Section: Resultsmentioning
confidence: 99%
“…If the rolling friction is included in the model, it makes the resistive forces reduce at a smaller rate and is able to finally take the plane to rest. Even with rolling friction, however, landing distances with no brakes are generally large because µ r is typically two orders of magnitude smaller than µ e for commercial airplanes and one order fot the UAVs tested [8].…”
Section: Equations Of Motionmentioning
confidence: 97%
See 1 more Smart Citation